Impact of common genetic variation on neonatal disease and outcome. Issue 5 (21st August 2007) - Harding, David
Abstract : The main aim of identifying gene–environment interactions is to provide insight into mechanisms of disease development and to identify patients with an inherent vulnerability to certain conditions. This in turn may allow patients to be targeted with individualised treatment based on the knowledge of their inborn susceptibility to specific conditions. This review describes the possible effects of common genetic variation on outcome in various conditions affecting the neonate. It focuses predominantly on studies of positive association rather than non-association to illustrate this potential influence and to highlight the potential for further study and intervention. The shortcomings of published association studies and the place of such studies in future research are also discussed.